Role of Tacrolimus C/D Ratio in the First Year After Pediatric Liver Transplantation - Prusinskas, Benas; Ohlsson, Sinja; Kathemann, Simone; Pilic, Denisa; Kampmann, Kristina; Büscher, Rainer; Paul, Andreas; Pape, Lars; Hoyer, Peter F.; Lainka, Elke (Frontiers in Pediatrics, 2021)
Background: Tacrolimus (TAC) is a calcineurin inhibitor (CNI), widely used as a cornerstone of immunosuppressive therapy after pediatric liver transplantation (LTX). Adverse effects, such as nephrotoxicity, limit the usage of CNI. The calculation of TAC metabolism rate helps to estimate an individual risk for therapy associated complications in adults. Methods: A retrospective, descriptive data analysis was performed in children, who underwent LTX 2009-2017 and received TAC twice daily in the first year after LTX. A weight adjusted concentration/dose ratio (C/D ratio) was calculated (TAC trough level / (daily TAC dose / body weight)) every three months after LTX to estimate an average individual TAC metabolism rate. According to C/D ratio all patients have been divided into two groups: fast metabolizers (FM) and slow metabolizers (SM). Clinical and laboratory parameters have been analyzed as risk factors in both groups. Results: 78 children (w 34, m 44, median age at LTX 2.4 (0.4 – 17.0) years) were enrolled in the study. FM (SM) had a mean C/D ratio of <51.83 (≥51.83) ng/ml / (mg/kg). FM were younger at the time of LTX (median age 1.7 (0.4 -15.8) years) than SM (5.1 (0.4 – 17.0), p = 0.008). FM had more often biliary atresia (20/39, 51 %) than SM (11/39, 28 %), p = 0.038, while SM had more often progressive familial intrahepatic cholestasis (PFIC) (9/39, 23 %) than FM (1/39, 3 %), p = 0.014. FM developed EBV-infection more often (27/39 (69 %)) than SM (13/39 (33 %), p = 0.002). 3 FM developed post-transplant lymphoproliferative disorder (PTLD). Annual change of renal function (eGFR) did not differ in both groups (slope FM 1.2 ± 0.6; SM 1.4 ± 0.8 ml/min/1.73 m² per year, p = 0.841). Conclusions: Calculation of individual, weight adjusted TAC C/D ratio is a simple, effective and cost-efficient tool for physicians to estimate the risk for therapy associated complications and to initiate individual preventive adjustments after pediatric LTX. In FM, lower levels of TAC are tolerable, especially in the presence of EBV infection, lower renal function or in the first two years of life.